Fiber-type phenotype of the jaw-closing muscles in Gorilla gorilla, Pan troglodytes, and Pan paniscus: A test of the Frequent Recruitment Hypothesis. Issue 151 (February 2021) - Taylor, Andrea B.; Holmes, Megan A.
Abstract: Skeletal muscle fiber types are important determinants of the contractile properties of muscle fibers, such as fatigue resistance and shortening velocity. Yet little is known about how jaw-adductor fiber types correlate with feeding behavior in primates. Compared with chimpanzees and bonobos, gorillas spend a greater percentage of their daily time feeding and shift to herbaceous vegetation when fruits are scarce. We thus used the African apes to test the hypothesis that chewing with unusually high frequency is correlated with the expression in the jaw adductors of a high proportion of type 1 (slow, fatigue-resistant) fibers at the expense of other fiber types (the Frequent Recruitment Hypothesis). We used immunohistochemistry to determine the presence and distribution of the four major myosin heavy chain (MHC) isoforms in the anterior superficial masseter (ASM), superficial anterior temporalis, and deep anterior temporalis of four Gorilla gorilla, two Pan paniscus, and four Pan troglodytes . Serial sections were stained against slow (MHC-1/-α-cardiac) and fast (MHC-2/-M) fibers. Fibers were counted and scored for staining intensity, and fiber cross-sectional areas (CSAs) were measured and used to estimate percentage of CSA of each MHC isoform. Hybrid fibers accounted for nearly 100% of fiber types in the masseter and temporalis of all three species, resulting in three main hybrid phenotypes. As predicted, the gorilla ASM and deep anterior temporalis comprised a greater percentage of CSA of the slower, fatigue-resistant hybrid fiber type, significantly so for the ASM ( p = 0.015). Finally, the results suggest that fiber phenotype of the chewing muscles contributes to behavioral flexibility in ways that would go undetected in paleontological studies relying solely on morphology of the bony masticatory apparatus.